Researching school practices with a complementary and symmetrical approach - the case of remote teaching in the rural north of Sweden - J Ola Lindberg; Jörgen From; Tomas Holmgren; Petter Lundberg; Gerd Pettersson; Fanny Pettersson; Linda Rudolfsson; Tobias Thomson (University of Aberdeen, School of Education, 2020)
This feature describes an ongoing research project on remote teaching in the rural north of Sweden. Remote teaching is a form of teaching in which the teacher and students are separated in space but not in time, and students are accompanied by a designated supervisor at their location. The project is conducted within the framework of the national initiative Development, Learning, Research (DLR) to try out sustainable collaboration models between academia and school practice. At Umeå University, this relation has been described as complementary and symmetrical: complementary in the sense that each part brings unique competencies into the work, and symmetrical in the sense that each part is valued as equal in the work, which allows for a dimension of development work into the research approach. The feature elaborates on opportunities and challenges in conducting complementary and symmetrical research, seeking to promote knowledge built on collaboration between academia and school practice.